2016
DOI: 10.4238/gmr.15017335
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between multiple paternity and reproductive parameters for Podocnemis sextuberculata (Testudines: Podocnemididae) in the Trombetas River, Brazil

Abstract: ABSTRACT. Genetic studies of multiple paternity are a valuable tool to gain information on the reproductive biology of turtles. We analyzed paternity type in Podocnemis sextuberculata and related number of fathers per nest to nesting period (beginning, middle, or end of nesting season); clutch size (number of eggs); female size; and hatchling success. Females were captured and maximum linear carapace lengths measured during the 60 days that encompass the nesting season at Rio Trombetas Biological Reserve (Pará… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The multiple paternity rate in the present study is, thus, in agreement with data reported in previous studies, in which Podocnemis expansa was found to be a species with polyandrous reproductive behavior (Valenzuela, 2000;Pearse et al, 2006). This behavior has also been reported as predominant in other reptiles, such as crocodilians (Oliveira et al, 2010), lizards (Oppliger et al, 2007), snakes (Madsen et al, 2005), and chelonians (Pearse et al, 2002;Roques et al, 2006;Fantin et al, 2008;Fantin et al, 2010;Freda et al, 2016). Although polyandry occurs in a large part of the reptile group, it is intriguing that the female turtles do not derive direct benefits from this behavior.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The multiple paternity rate in the present study is, thus, in agreement with data reported in previous studies, in which Podocnemis expansa was found to be a species with polyandrous reproductive behavior (Valenzuela, 2000;Pearse et al, 2006). This behavior has also been reported as predominant in other reptiles, such as crocodilians (Oliveira et al, 2010), lizards (Oppliger et al, 2007), snakes (Madsen et al, 2005), and chelonians (Pearse et al, 2002;Roques et al, 2006;Fantin et al, 2008;Fantin et al, 2010;Freda et al, 2016). Although polyandry occurs in a large part of the reptile group, it is intriguing that the female turtles do not derive direct benefits from this behavior.…”
Section: Discussionsupporting
confidence: 93%
“…Fantin et al (2008) found multiple paternity in six nests of a Podocnemis unifilis population on the Amazon River (municipality of Barreirinha, state of Amazonas, Brazil) using eight microsatellite loci, demonstrating the contribution of at least two male turtles to each brood. Freda et al (2016) also found multiple paternity in seven Podocnemis sextuberculata nests on the Amazon River by using six microsatellite loci, demonstrating at least two male contributors to each brood. In another study, Fantin et al (2010) analyzed six Podocnemis erythrocephala nests by using four microsatellite loci and found the participation of more than two male turtles.…”
Section: Discussionmentioning
confidence: 76%
“…Subgroup meta-analysis of Testudines included Gopherus polyphemus (Testudinidae) (Moon et al 2006;Tuberville et al 2011;White et al 2018), Podocnemis sextuberculata (Podocnemididae) (Freda et al 2016) and species of Cheloniidae: Chelonia mydas (Lee and Hays 2004;Wright et al 2013;Alfaro-Núñez et al 2015;Turkozan et al 2019), Eretmochelys imbricata (Phillips et al 2014), Caretta caretta (Sari et al 2017), Natator depressus (Theissinger et al 2009) and Lepidochelys olivacea (Hoekert et al 2002;Jensen et al 2006). This resulted in a non-significant summary effect size (Fig.…”
Section: Tablementioning
confidence: 99%